Shade affects magnitude and tactics of juvenile Chinook salmon antipredator behavior in the migration corridor - Megan C. Sabal; Michelle L. Workman; Joseph E. Merz; Eric P. Palkovacs (Oecologia, 2021)
Environmental conditions strongly affect antipredator behaviors; however, it is less known how migrating prey adjust antipredator behavior in migration corridors, in part, because active migrants are difficult to observe and study. Migrants are vulnerable and encounter many predators in the corridor, and their propensity to travel towards their destination ties antipredator behavior with movement. We evaluated how environmental risk cues in the migration corridor including in-water habitat structure (present, absent) and overhead shade (sun, shade), and salmon origin (hatchery, wild) affected how juvenile Chinook salmon ( Oncorhynchus tshawytscha ) reacted to a live predator. We measured how salmon react to predation risk as the difference in time to swim downstream through a 9.1-m long field enclosure with or without a live predatory largemouth bass ( Micropterus salmoides ). Shade significantly modified the reaction to the predator, and it did so in two ways. First, the magnitude of antipredator behavior was larger in shade compared to direct sun, which suggests salmon perceived shade to be a riskier environment than sun. Second, the escape tactic also varied; salmon slowed down to be cautious in shade and sped up in sun. Structure did not significantly affect behavior and hatchery and wild salmon behaved similarly. Our study suggests that environmental risk cues can shape the magnitude and tactics of how migrants react to predation risk and illustrates how these responses relate to movement with potential to scale up and affect migration patterns.

Migration characteristics of hatchery and natural-origin Oncorhynchus mykiss from the lower Mokelumne River, California - S. Casey Del Real; Michelle Workman; Joseph Merz (Environmental Biology of Fishes, 2012)